Didactics: Peculiarities of Motor Skills Development in Boys Aged 14-15 - Oleg Khudolii; Pavol Bartík; Dmytro Ivanov; Andrii Bezzub (OVS LLC, 2021)
The purpose of the study was to determine the peculiarities of motor skills development in boys aged 14-15. Materials and methods. The study participants were boys aged 14 (n=20) and 15 (n=20). The children and their parents were fully informed about all the features of the study and gave their consent to participate in the experiment. To solve the tasks set, the following research methods were used: study and analysis of scientific and methodological literature; pedagogical observation, timing of training tasks; pedagogical experiment, methods of mathematical statistics, discriminant analysis, nearest neighbor analysis. Results. The study made an assumption about a significant influence of the modes of alternating exercise repetitions and the rest interval on the effectiveness of motor skills development in boys aged 14 and 15. The standardized canonical discriminant function coefficients helped to determine age peculiarities and the peculiarities of influence of exercise modes on the effectiveness of motor skills development. They showed that the components of motor fitness are a priority in developing motor skills. The structure canonical discriminant function coefficients indicate the importance of movement control skills for mastering the entire exercise. Conclusions. Discriminant analysis revealed the peculiarities of motor skills development in boys aged 14 and 15, depending on age and exercise modes. With the first exercise mode, boys aged 15 master the first, second, and fourth series of training tasks more quickly. Boys aged 14 - the sixth series (exercise mode: 6 repetitions, rest interval of 60 s). With the second exercise mode, boys aged 14 master the first and fourth series of training tasks more quickly. Boys aged 15 - the second series (exercise mode: 12 repetitions, rest interval of 60 s). The coordinates of centroids for four groups indicate a significant difference in the influence of exercise repetition modes on the number of repetitions required for motor skills development in boys aged 14-15 during physical education classes. The results of group classification show that 87.5% of the original grouped cases were classified correctly.